Impactos macroeconômicos sobre a formação de bolhas especulativas no mercado agropecuário brasileiro - Cabrine, Carlos Guilherme das Neves (Universidade Federal de São Carlos, 2023)
The volatility in commodity prices has direct implications for the financial results of companies and consumers. Not infrequently, such variations occur in a sharp way, and in non-compliance with market fundamentals, that is, in a speculative way. When this occurs, the effects on agents' expectations are even greater, as it negatively affects the price discovery and hedging processes. The main objective of the work is to identify the occurrence of speculative bubbles in the prices of selected commodities, also trying to determine the reason for the existence of such movements. For this, we used daily price series of the three most liquid commodities (feeder cattle, corn, coffee) traded on the Brazilian commodities and futures exchange market, B³, as well as macroeconomic variables (interest rate, exchange rate, economic activity index, money supply as a percentage of the GDP, stock index Bovespa, brazilian consumer price index), for the period between 2013 and 2021. The Generalized Supreme Augmented Dickey-Fuller (GSADF) and Backward Supreme Augmented Dickey-Fuller (BSADF) tests were used to detect and datestamp the explosive periods in prices, and the Poisson regression model for inspection and understanding of the determining macroeconomic factors in the formation of bubbles. As a result, slightly explosive processes were found in all commodities for the analyzed period, although infrequent. Concerning the macroeconomic effects, money supply, stock index and inflation had a positive impact on the emergence of bubbles, while interest rates and economic growth had negative effects.
Macroeconomic impacts on the formation of speculative bubbles in the brazilian agricultural market
Keywords: Mercado Futuro; Bolha Especulativa; Commodities Agropecuárias; Macroeconomia; Future Market; Speculative Bubbles; Agricultural Commodities; Macroeconomics; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS